2022
DOI: 10.1117/1.apn.1.2.026001
|View full text |Cite
|
Sign up to set email alerts
|

Deep-tissue two-photon microscopy with a frequency-doubled all-fiber mode-locked laser at 937 nm

Abstract: In two-photon microscopy, low illumination powers on samples and a high signal-to-noise ratio (SNR) of the excitation laser are highly desired for alleviating the problems of photobleaching and phototoxicity, as well as providing clean backgrounds for images. However, the high-repetition-rate Ti: sapphire laser and the low-SNR Raman-shift lasers fall short of meeting these demands, especially when used for deep penetrations. Here, we demonstrate a 937-nm laser frequency-doubled from an all-fiber mode-locked la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A typical 40‐MHz fiber laser requires 20 times more energy to penetrate tissue to a similar depth. [ 31 ]…”
Section: Innovations In Multiphoton Microscopymentioning
confidence: 99%
“…A typical 40‐MHz fiber laser requires 20 times more energy to penetrate tissue to a similar depth. [ 31 ]…”
Section: Innovations In Multiphoton Microscopymentioning
confidence: 99%
“…The emergence of ultrafast laser pulse generation, a milestone in laser science, has triggered incredible progress across a wide array of disciplines, encompassing industrial applications, energy technologies, life sciences, and beyond 1 , 2 . Cutting-edge innovations, such as robust laser ignition systems, 3 vibrant laser 3D printing, 4 mind-boggling attosecond science, 5 and high-resolution microscopic imaging, 6 are effectively powered by ultrafast lasers. Among the various laser platforms that have been developed, fiber oscillators, esteemed for their compact design, outstanding performance, and cost-effectiveness, have become one of the mainstream technologies for generating femtosecond laser pulses 7 …”
Section: Introductionmentioning
confidence: 99%
“…He et al demonstrated a high-power all-fiber mode-locked laser at 1870 nm. The maximum output power of femtosecond laser is 341 mW at a pump power of 4.5 W [9]. However, to realize the short-wavelength operation of the TDF laser, short length of active fiber and high excitation densities need to be used to reduce the reabsorption in TDF, which result in significant power loss.…”
Section: Introductionmentioning
confidence: 99%